THE DECENTRALIZATION METHOD AS A TOOL TO IMPLEMENT SOCIAL INITIATIVES OF CITIZENS IN MULTINATIONAL STATES - D. Bunikowski; K. Ivanova (BRICS Law Journal, 2017)
In this article the decentralization process and decentralization method are reviewed. Decentralization is the process of redistributing or dispersing functions, powers, people or things away from a central location or authority. While centralization, especially in the governmental sphere, is widely studied and practiced, there is no common definition or understanding of decentralization. The meaning of decentralization may vary in part because of the different ways in which it is applied. In this article the concepts of decentralization are researched. Decentralization in any area is a response to the problems of centralized systems. Decentralization in government, the topic most studied, has been viewed as a solution to problems such as economic decline, government inability to fund services and the general decline in performance of overloaded services, the demands of minorities for a greater say in local governance, the general weakening legitimacy of the public sector, and global and international pressure on countries with inefficient, undemocratic, overly centralized systems. The authors also research the issues of personal federalism and the subsidiarity principle.